Hegel und der staat. - Rosenzweig, Franz, 1886-1929, author.
1 online resource
Keywords: "Franz Rosenzweig (1886-1929) is one of the most significant German Jewish philosophers of the twentieth century. Published in German in 1920 and now finally available in English for the first time, Hegel and the State is a major contribution to the understanding of Hegel's political and social thought and a profound analysis of the intellectual currents that shaped the German state in the late nineteenth and early twentieth centuries. Through careful readings of Hegel's early handwritten manuscripts, Rosenzweig shows that Hegel was wrestling with the problem of how to reconcile the subjectivity and freedom of the individual within a community and ultimately the political state. According to Rosenzweig, the route out of this conundrum chosen by Hegel shaped his mature political philosophy, where he saw the relationship between the individual and the state as reciprocal. At a deeper level, the significance of Hegel and the State lies in the way that Rosenzweig explains the failure of Hegel's quasi-communitarian view of the state to emerge, due to the authoritarian direction of the newly-unified German state under Bismarck. Anticipating the political and moral disaster that was to follow, Rosenzweig concludes by questioning the very viability of any theory of the state that relies on the pillars of bureaucratic militarism and a government-supported capitalist business culture. With the inclusion of a Foreword by Myriam Bienenstock and a substantial Afterword by Axel Honneth, Hegel and the State is a ground-breaking work of early twentieth-century philosophical and political thought. It is essential reading for students of Hegel, German Idealism, Jewish philosophy, and the origins of critical theory. It will also be of interest to those in related subjects such as the history of sociology, and German and intellectual history"--